Valuing collaborative synergies with real options application: From dynamic political capabilities perspective - Andrejs Čirjevskis (Journal of Risk and Financial Management, 2022)
This paper aims to justify propositions that the dynamic political capabilities of collaborative partners to manage their institutional contexts are important drivers of collaborative synergies which can be valued by real options. To date, the institutional context of collaborative corporate strategies (strategic alliances, mergers, and acquisitions), particularly the analysis of the influence of government agencies on the synergies or unrealized synergies of collaborative ventures, remains unexplored. Moreover, the interdependence between the institutional dimensions of the collaborative strategies, the dynamic political capabilities of the collaborating partners, and collaborative synergies are needed to be integrated into new conceptual models and a new framework. This paper contributes to this request by providing a cohesive framework of micro-foundations with dynamic political capabilities and demonstrating an application of simple and compound sequentially combined real options for collaborative synergies' valuation in the findings and discussion section. This paper makes several theoretical and empirical contributions to international business, strategic management, and corporate finance. The practical implication of the research is evidence that food retailers who want to grow with the latest consumer trends will need dynamic political capabilities to deal with the impact of an institutional context. Finally, this paper discusses research limitations and future work.
Keywords: 650; collaborative synergy; compound real option; dynamic political capabilities; international alliance; mergers and acquisitions; micro-foundations; simple real option